Seismic Assessment of a Masonry Building in Patan, Nepal - Acharya, Abiskar; Dahal, Alok; Jha, Aashutosh Kumar; Mainali, Angel; Thagunna, Amar Singh; Pathak, Asal Babu; Adhikari, Rabindra (Journal of Engineering Issues and Solutions, 2026)
Nepal’s cultural heritage, especially the traditional masonry structures found in UNESCO World Heritage sites like Patan, is seriously threatened by the country’s high seismicity. Many of these buildings were constructed using pre-code methods, such as unreinforced brick masonry with mud mortar, which made them extremely vulnerable to the 2015 Gorkha earthquake. The actual as-built conditions and structural behavior of such heritage buildings are frequently not reflected in Nepal’s current seismic risk models. By conducting a thorough seismic performance evaluation of a typical traditional brick building in Patan, this study fills this gap. Laboratory testing was used to determine the brick’s compressive strength, and field surveys were utilized for the case study’s selection and geometric characterization. Nonlinear static pushover analyses were performed in the two principal directions using a three-dimensional finite element model created in DIANA FEA 10.5. With a base shear of 410 kN at an ultimate displacement of 36.5 mm in the X-direction and 236 kN at 65.5 mm in the Y-direction, the results show a strong directional dependence of seismic capacity. Fundamental periods of 0.594 and 0.388 seconds were found by eigen value analysis. Four damage states were linked to roof displacement through the development of fragility curves. Analysis using the Capacity Spectrum Method against NBC 105:2020 demand spectra shows extremely high vulnerability, with collapse expected under stronger shaking and collapse prevention limits exceeded at PGA levels as low as 0.1g. For Patan’s traditional masonry buildings, the results offer vital, region-specific fragility and capacity data that support well-informed risk mitigation, retrofitting techniques, and heritage conservation planning.